Converting Words: Maya in the Age of the Cross - Hanks, William F. (The Anthropology of Christianity, 2010)
This pathbreaking synthesis of history, anthropology, and linguistics gives an unprecedented view of the first two hundred years of the Spanish colonization of the Yucatec Maya. Drawing on an extraordinary range and depth of sources, William F. Hanks documents for the first time the crucial role played by language in cultural conquest: how colonial Mayan emerged in the age of the cross, how it was taken up by native writers to become the language of indigenous literature, and how it ultimately became the language of rebellion against the system that produced it. Converting Words includes original analyses of the linguistic practices of both missionaries and Mayas-as found in bilingual dictionaries, grammars, catechisms, land documents, native chronicles, petitions, and the forbidden Maya Books of Chilam Balam. Lucidly written and vividly detailed, this important work presents a new approach to the study of religious and cultural conversion that will illuminate the history of Latin America and beyond, and will be essential reading across disciplinary boundaries.